2015
DOI: 10.1038/ncomms8785
|View full text |Cite
|
Sign up to set email alerts
|

Gains and losses of coral skeletal porosity changes with ocean acidification acclimation

Abstract: Ocean acidification is predicted to impact ecosystems reliant on calcifying organisms, potentially reducing the socioeconomic benefits these habitats provide. Here we investigate the acclimation potential of stony corals living along a pH gradient caused by a Mediterranean CO2 vent that serves as a natural long-term experimental setting. We show that in response to reduced skeletal mineralization at lower pH, corals increase their skeletal macroporosity (features >10 μm) in order to maintain constant linear ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
123
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 109 publications
(148 citation statements)
references
References 29 publications
14
123
4
1
Order By: Relevance
“…Stylophora pistillata, for example, exploits this strategy when growing at low pH (7.2), which results in depressed calcification, by increasing skeletal porosity (Tambutté et al 2015). A similar trend has been reported for the temperate coral Balanophyllia europaea (Fantazzini et al 2015).…”
Section: Discussionsupporting
confidence: 51%
“…Stylophora pistillata, for example, exploits this strategy when growing at low pH (7.2), which results in depressed calcification, by increasing skeletal porosity (Tambutté et al 2015). A similar trend has been reported for the temperate coral Balanophyllia europaea (Fantazzini et al 2015).…”
Section: Discussionsupporting
confidence: 51%
“…(ii) The net calcification rate of the symbiotic B. europaea was not affected by decreasing pH, regardless of temperature, while for the two asymbiotic species L. pruvoti and A. calycularis it was negatively affected by decreasing pH and increasing temperature, suggesting that B. europaea may be more tolerant to increasing acidity compared to the other two species. Investigations at Panarea3031 and Ischia CO 2 vents2971 have shown that at pH TS 7.8, an ecological tipping point occurs as corals and mollusks disappear below this threshold. Our in situ transplant experiment is in agreement with this tipping point as in most cases we reported the highest mortality and the lowest calcification rates at mean pH TS  ≤ 7.7.…”
Section: Discussionmentioning
confidence: 99%
“…Gross calcification rate (CaCO 3 production by the coral) of B. europaea transplanted at CO 2 vents off Ischia, decreased with increasing acidity when the water was warmest29. Moreover, B. europaea naturally occurring at a CO 2 vent off Panarea, under long-term exposure to acidic conditions, shows a significant decrease in population density and net calcification rate, accompanied by an increase in skeletal porosity, with increasing acidity3031. This suggests that OA could likely exacerbate the mass benthic mortality events already recorded in the warming Mediterranean Sea, making it crucial to study the possible interactive effects between increasing sea temperature and acidity on coral mortality and growth rates.…”
mentioning
confidence: 99%
“…There is also evidence that the structural integrity of any reef framework is compromised due to a loss of architectural complexity (Fabricius et al, 2011), increased rates of bioerosion (Enochs et al, 2016a,b), reductions in coral growth (Fabricius et al, 2011) and reduced skeletal density (Fantazzini et al, 2015;Strahl et al, 2015b).…”
Section: Co 2 Ventsmentioning
confidence: 99%